Clinical research informatics - Andrews, James E.; Richesson, Rachel L. (Health Informatics, 2012)
Clinical research informatics (CRI) is the application of informatics principles and techniques to support the spectrum of activities and business processes that instantiate clinical research. Informatics, defined generally as the intersection of information and computer science with a health-related discipline, has a foundation drawn from many well-established, theory-based disciplines, including computer science, library and information science, cognitive science, psychology, and sociology. The newly articulated yet fundamental theorem of informatics states that information technology should be used to enable humans to function and perform better together than humans alone, and so informatics is a source for supportive technologies and tools that enhance - but not replace - unreservedly human processes. Clinical Research Informatics contributes to the ongoing dialogues among researchers and practitioners in CRI as they continue to rise to the challenges of a dynamic and evolving clinical research environment. The development of CRI as a sub-discipline of informatics, and as an independent/maturing professional practice area in its own right, drives a growing pool of scientific literature based on original CRI research, and high-impact tools and systems will be developed. CRI leaders and stakeholder groups will continue to support and create communities of discourse that will address much needed practice standards in CRI, improved safety and efficiencies in clinical research, data standards in clinical research, policy issues, educational standards and instructional resources. The Editors and contributors to this book are among the most active and engaged in the CRI domain and provide an excellent primer for deeper explorations into this emerging discipline. Certain themes are highlighted, including the changing role of the consumer, movement toward transparency, growing needs for global coordination and cooperation on many levels, and the merging together of clinical care delivery and research as part of a changing paradigm in global healthcare delivery - all in the context of rapid innovations in technology and explosions of data sources, types, and volume. This book is therefore of considerable interest to all students of biomedical informatics, from the newcomer to the professional informatician.